Fetal Wound Healing Biomarkers - Helmo, Fernanda Rodrigues; Machado, Juliana Reis; Guimarães, Camila Souza de Oliveira; Teixeira, Vicente de Paula Antunes; Reis, Marlene Antônia dos; Corrêa, Rosana Rosa Miranda (Disease Markers, 2013)
Fetal skin has the intrinsic capacity for wound healing, which is not correlated with the intrauterine environment. This intrinsic ability requires biochemical signals, which start at the cellular level and lead to secretion of transforming factors and expression of receptors, and specific markers that promote wound healing without scar formation. The mechanisms and molecular pathways of wound healing still need to be elucidated to achieve a complete understanding of this remodeling system. The aim of this paper is to discuss the main biomarkers involved in fetal skin wound healing as well as their respective mechanisms of action.